Phase transformations in radiolytically formed manganese nano-oxide. (November 2021) - Puspalata, R.; Mal, Debasis; Balaji, V.; Chandramohan, P.; Amirthapandian, S.; Ganesan, Rajesh; Krishna Mohan, T.V.
Abstract: Nano-crystalline oxides of manganese prepared from the radiolysis of aqueous permanganic acid solution at ambient conditions showed structural and compositional changes with variation in absorbed gamma dose. The radiolytically formed nano-oxide was transformed into different micro-structures, phases, shapes and sizes with radiation. This variation was probed using X-ray powder diffraction (XRD), laser Raman spectroscopy (LRS) and transmission electron microscopy (TEM). At lower doses formation of a mixture of nano-oxides of Mn(OH)2, λ-MnO2 was detected from XRD analysis. This nano-oxide mixture changed to stable Mn3 O4 at higher doses. The maximum crystallite size was observed to be 15 nm. LRS results also supported this inference. This paper presents the detailed study on the phase transitions of the radiolytically formed nano-manganese oxides and the possibility of its use as radiation marker for predicting radiation response. Highlights: Nano-oxides of manganese were generated from radiolysis of HMnO4 . Dose-dependent phase transformation was observed from XRD, Raman and TEM analysis. Mn(OH)2 formed at lower doses were converted to stable Mn3 O4 via λ-MnO2 . Radiolytically formed manganese oxide has a potential for application in radiation detection/dosimeter. Maximum crystallite size observed from radiolysis of 2.5 mM HMnO4 was 15 nm.